1979
DOI: 10.1007/bf03189427
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and metabolism of [14C]loperamide in rats

Abstract: Following oral administration of [14C]loperamide hydrochloride in 1 mg/kg to rats, plasma levels of radioactivity reached maximum at 4 hrs and decreased with a half-life of 4.1 hrs. Radioactivity in 96-hr feces accounted for 95% of the dose, with 30% associated with unchanged drug, while that in urine only 3.5%. Radioactivity in 48-hr bile accounted for 42% of the dose associated entirely with metabolites. 3% of the dose was found at the level of the enterohepatic cycles. These findings show that about 70% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…The kinetic parameters for transport and metabolism were generated from the in vitro studies with intestinal tissue of the same strains of mice, which enabled proper design and interpretation of the in vivo experiments Loperamide, a m-opioid receptor agonist that is used in the treatment of diarrhea, was chosen as a probe compound for this study because it has a low oral bioavailability (Heykants et al, 1974;Miyazaki et al, 1979) that is attributed to efficient P-gp-mediated efflux (Schinkel et al, 1996;Acharya et al, 2006) and extensive CYP3A-mediated first-pass metabolism (Kim et al, 2004). In fact, a quantitative measure of efficiency of P-gp [AQ, eq.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic parameters for transport and metabolism were generated from the in vitro studies with intestinal tissue of the same strains of mice, which enabled proper design and interpretation of the in vivo experiments Loperamide, a m-opioid receptor agonist that is used in the treatment of diarrhea, was chosen as a probe compound for this study because it has a low oral bioavailability (Heykants et al, 1974;Miyazaki et al, 1979) that is attributed to efficient P-gp-mediated efflux (Schinkel et al, 1996;Acharya et al, 2006) and extensive CYP3A-mediated first-pass metabolism (Kim et al, 2004). In fact, a quantitative measure of efficiency of P-gp [AQ, eq.…”
Section: Discussionmentioning
confidence: 99%
“…The low efficacy of loperamide in our study could be related to a metabolic reaction due to drug interactions. Loperamide is mainly metabolized to desmethyl loperamide (DLOP) through the N-demethylation pathway [37,38], and clinical studies have shown that DLOP formed by LOP N-demethylation is a major metabolite of LOP in humans [39,40]. Moreover, it has been demonstrated that CYP2B6, CYP2C8, CYP2D6, and CYP3A4 catalyze LOP N-demethylation in human liver microsomes, and among them, CYP2C8 and CYP3A4 may play a crucial role in loperamide N-demethylation at therapeutic concentrations [41].…”
Section: Discussionmentioning
confidence: 99%
“…blood draw, the animal was sacrificed by decapitation and the brain harvested. This time point was chosen based on reported Lop pharmacokinetic studies in rats 16; 17 along with our pilot study in rats. Collectively, the literature and our pilot study results indicate that this duration was adequate for Lop and its metabolite, dLop, to reach pseudo-equilibrium between the brain and plasma, and exhibit linear pharmacokinetics at the Lop, dLop plasma concentrations studied 16; 17; 18 .…”
Section: Methodsmentioning
confidence: 99%